2014
DOI: 10.3109/09513590.2014.945759
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health of adolescents in Russia: statistics, problems and prospects of improvement

Abstract: At the beginning of the 21st century we still face the problem of reproductive health of women, children and adolescents in Russia. Final overcoming of the "Russian Cross" primarily relates to preventing further decline of women in reproductive age and children aged 0-17 years.The following medico-social determinants of women's reproductive health are considered: family prosperity, somatic growth and sexual maturation, chronic extragenital diseases, sexual and reproductive behavior, environmental wellbeing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[18,32,33] (see Figure 2) and many will have had more than one partner. [32][33][34][35] In the Canadian Community Health Survey, [32] 35% of 15-to 17-year-old and 39% of 18-to 19-year-old adolescents reporting having sex with more than one partner. In Finland, Leikko et al [33] report that, by the age of 22 years, 53% of women will have had five partners or more, irrespective of the age they first had sexual intercourse.…”
Section: Global Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,32,33] (see Figure 2) and many will have had more than one partner. [32][33][34][35] In the Canadian Community Health Survey, [32] 35% of 15-to 17-year-old and 39% of 18-to 19-year-old adolescents reporting having sex with more than one partner. In Finland, Leikko et al [33] report that, by the age of 22 years, 53% of women will have had five partners or more, irrespective of the age they first had sexual intercourse.…”
Section: Global Challengesmentioning
confidence: 99%
“…Estimates from four national US surveys conducted between 1988 and 1997 showed that almost 20% of adolescent women aged 15-17 years had two or more sexual partners in the previous three months. [34] Data from an anonymous survey conducted amongst 3327 Russian females aged between 13 and 19 years show that 25% have had three or more sexual partners by the age of 19 [35] and almost one in five report having an ongoing sexual relationship with two or more partners at the same time. [35] The age at first intercourse influences the likelihood of using contraception.…”
Section: Global Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular attention should be drawn to girls at the pubertal period, since adolescents require vitamin D supplements during their intensive growth, but they extremely rare take low-dose Vitamin D to prevent deficiency [35].…”
Section: Correction Of Vitamin D Deficiency As Prevention Of Menstruamentioning
confidence: 99%